The Perlon Unggahan Ritual: Understanding Gender Equality in the Blangkon Islamic Community (Study in Pakuncen Village, Jatilawang District, Banyumas Regency) - Qembig Al Gezon; Aulia Fauziah Aldi; Nabilla Poetri Andini; Alizar Isna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
This research aims to describe the division of the roles of men and women in the ritual procession of the Perlon unggahan of the Blangkhon Islamic community, and to describe the meaning of the division of the roles of men and women in the ritual of the Perlon unggahan of the Blanghon Islamic community. This research uses a qualitative method. Data collection methods were carried out by means of in-depth inter- views, observation, documentation studies, and literature studies. The results of the study show that one of the main values in the ritual of the Perlon unggahan is respect for women, that women are representatives of God because humans are born in the world through female intermedi- aries. This main value shows the existence of gender equality in the ritual of the Perlon unggahan where male followers do not dominate and women are not considered subordinated, because there are unique roles that can- not be performed by men such as women being allowed to purify them- selves and come to Kyai Bonoheling’s grave first, in the past while the men were in charge of coohing. In addition, men and women are treated equally, namely walhing barefoot carrying produce of the earth from the Cilacap Regency area to Pehuncen Village, Banyumas Regency. Both men and women are given the freedom to follow the ritual according to their wishes, without any coercion and social sanctions.